Penguatan UMKM Takso By Freyfood Melalui Transformasi Digital dan Sistem Keuangan: Pengabdian - Clara Ayu Lestari; Laelani Safitri; Reha Izan Zakiah; Fitri SM.,MM (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen the Takso By Freyfood MSME through the implementation of digital transformation and a more structured financial system to improve business efficiency and competitiveness. This MSME faces various problems, including limited digital marketing, manual financial record keeping, low production capacity, and limited human resources in business management. The implementation method includes field observations, structured interviews with business owners, training, and mentoring through simulations of digital application usage. The mentoring focused on implementing simple financial records based on Microsoft Excel, optimizing digital marketing through social media platforms like Instagram and TikTok, improving the quality of promotional content, and improving business operational management. The results of the activity showed an increase in business owners’ understanding of more organized and systematic financial management, expanding digital marketing reach, and increasing efficiency in operational processes. Overall, this community service activity has a positive impact on improving the performance and competitiveness of the Takso By Freyfood MSME in a sustainable manner.